The relationship between the social management of emotional intelligence and academic performance among medical students - Chew, Boon How; Md. Zain, Azhar; Hassan, Faezah (Routledge, 2015)
Positive social interaction with peers was said to facilitate cognitive and intellectual development leading to good academic performance. There was paucity of published data on the effect of social management (SM) emotional intelligence (EI) on academic performance. We conducted this study to examine their relationship in the undergraduate medical students in a public medical school in Malaysia. This was a cross-sectional study using the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) to measure the SM. The first and final year medical students were invited to participate. Students answered a paper-based demography questionnaire and completed the online MSCEIT in privacy. Independent predictors were identified using multivariate analyses. A total of 163 (84 first year and 79 final year) medical students completed the study (at a response rate of 66.0%). SM score (B = -.10 95% CI -.175 to -.015, p = .021) was significantly related to the continuous assessment (CA) marks (adjusted R(2) = .45, F13,137 = 10.26, p < .0001), and was a predictor of poor result in the overall CA (adjusted OR 1.06 95% CI 1.011-1.105). Negative relationships might exist between emotional social intelligence and academic success in undergraduate medical students. A different collection of social skills and SM EI could be constructive towards academic achievement in medical schools.